2009
DOI: 10.1146/annurev.physchem.040808.090420
|View full text |Cite
|
Sign up to set email alerts
|

Principles and Progress in Ultrafast Multidimensional Nuclear Magnetic Resonance

Abstract: Multidimensional acquisitions play a central role in the progress and applications of nuclear magnetic resonance (NMR) spectroscopy. Such experiments have been collected traditionally as an array of one-dimensional scans, with suitably incremented delay parameters that encode along independent temporal domains the nD spectral distribution being sought. During the past few years, an ultrafast approach to nD NMR has been introduced that is capable of delivering any type of multidimensional spectrum in a single t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
95
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 72 publications
0
95
0
Order By: Relevance
“…It is interesting to compare these spontaneous polarization transfer processes with analogs based on J-transfers, discussed in the hyperpolarized literature [8,[10][11][12][13][25][26][27][28]. Although it is likely that coherent transfer sequences like INEPT could lead to larger single-shot 1 H signals, the mechanism here presented evidences a number of advantageous features.…”
Section: Discussionmentioning
confidence: 84%
“…It is interesting to compare these spontaneous polarization transfer processes with analogs based on J-transfers, discussed in the hyperpolarized literature [8,[10][11][12][13][25][26][27][28]. Although it is likely that coherent transfer sequences like INEPT could lead to larger single-shot 1 H signals, the mechanism here presented evidences a number of advantageous features.…”
Section: Discussionmentioning
confidence: 84%
“…Central in the development of these new experiments is the spatiotemporal manipulation of the spin interactions, a concept that originated from a search for methods capable of delivering arbitrary multidimensional MR spectra in a single scan (10,11). The generality of the ensuing approach eventually led to several new routes for executing single-scan multidimensional MRI (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Advances in fast data collection in NMR spectroscopy (16,17) suggested that it may be possible to monitor conformational changes of riboswitches, which occur with relatively slow time course of seconds (8,12), using real-time multidimensional NMR. Here we report the successful collection of 2D ultraSO-FAST NMR spectra (18), recorded at repetition rates of about 0.5 Hz, to follow the complete conformational change from ligand-free to ligand-bound form of the adenine riboswitch.…”
mentioning
confidence: 99%